The role of O- and S-containing surface groups on carbon nanotubes for the elimination of organic pollutants by catalytic wet air oxidation - Raquel P. Rocha (2014)
Multi-walled carbon nanotubes (CNTs) were subjected to several liquid-phase chemical treatments (using HNO3, H2SO4, a mixture of HNO3/H2SO4, HCI or bubbling O-3 in water) as well as gas-phase thermal treatments under nitrogen atmosphere (at 200, 400 and 600 degrees C) in order to obtain CNTs with different chemical properties. The modified CNTs were characterized by common techniques including nitrogen adsorption at -196 degrees C, temperature programmed desorption, thermogravimetry, X-ray photoelectron spectroscopy and point of zero charge (pH(pzc).). The HNO3 and HNO3/H2SO4 treatments induced a pronounced acidic character to the pristine CNTs (originally with a neutral pH(pzc), of 6.8), creating a large amount of carboxylic acids, anhydrides and phenol surface groups, and also lactones and carbonyl/quinone surface groups. The treatment with H2SO4 alone, or with the HNO3/H2SO4 mixture, led to the additional introduction of S-containing groups (such as sulphonic groups), while O-3 and HCl treatments did not affect significantly the surface chemistry. The pristine and modified CNTs were studied as catalysts in the catalytic wet air oxidation (CWAO) process by using oxalic acid and phenol as model pollutants (at 140 and 160 degrees C, respectively, and 40 bar of total pressure). At the selected operating conditions, these pollutants are quite stable in the absence of a catalyst. However, a marked degradation of both compounds was observed in the presence of CNTs. The O-containing surface groups in CNTs (carboxylic acids, phenols, anhydrides) contribute to the acidic character of the surface, and, simultaneously, decrease the catalytic activity for degradation of the tested pollutants. The presence of S-containing groups also increases the acidity of the CNTs, but a marked increase of the catalytic activity was observed in this particular case (complete degradation of the pollutants, 56% of TOC reduction in 120 min when phenol was the pollutant, and complete mineralization of oxalic acid). Therefore, the presence of S-containing groups and the absence of carboxylic groups (such as carboxylic acids and anhydrides) seem to improve the catalytic performance of CNTs; however, the S-containing materials are not stable in consecutive runs, probably as a result of the high temperatures and pressures employed in the CWAO process.